As destaladeiras que cantam: produção de material didático para EJA em Arapiraca (Alagoas) - Oliveira, Rafael Cardoso de (2023)
The problem of this work is the absence of didactic materials for the Teaching of Local History in the Education of Young People and Adults in the Municipal Public Education Network of Arapiraca - Alagoas. Its justification consists in giving voice to characters silenced in the discourse of Progress and Development of the City. To that extent, it makes a decisive contribution to student learning from its use by history teachers. Its objective is to create a reference to guide the elaboration of a Notebook of Didactic Sequences: The Workers Who Sing Arapiraca, intended for use by teachers who teach classes in EJA. The Notebook, the pedagogical product of this dissertation is aimed at EJA, as students of this modality, specifically in the 5th phases and in module 3 of the modular EJA, can have a more sensitive relationship with the tobacco culture, which still exists in different points of the city. In general, teachers of this modality do not receive didactic materials that support their actions, finding themselves in situations of need for complementary instruments to improve their pedagogical interventions. In this sense, the objective is also to strengthen these pedagogical relationships with strong support from subsidies about Local History, precisely the tobacco slicers that sang.